Collects of the Roman missals : a comparative study of the Sundays in proper seasons before and after the Second Vatican Council /: a comparative study of the Sundays in proper seasons before and after the Second Vatican Council. (2013 copyright 2013) - Pristas, Lauren
No abstract available